The Mediating Role of the Entrepreneurial Intention in the Relationship between Critical Thinking and Employee productivity Telecommunication Company of Isfahan - Rezaei, Nooshin; Peykani, Mehraban Hadi (International Review of Management and Marketing, 2017)
This study aimed to determine the mediating role of the entrepreneurial intention in the relationship between critical thinking and employee productivity Telecommunication Company of Isfahan with descriptive and correlational method. The population included all experts and managers of Telecommunications Company of Isfahan in 2016. The total number was equal to 1020 and based on Krejcie and Morgan table, 278 individuals were selected through convenience sampling method. A questionnaire was used to collect data. Spss19 and structural equation modeling software Amos23 were used to analyze the research data. The results showed that there is a significant direct relationship between critical thinking, employee productivity and entrepreneurial intention. Moreover, the mediation demonstrated that entrepreneurial intention plays a partial mediating role between critical thinking and employee productivity. In addition to these results, research indicates that there are significant differences between respondents’ views with regard to employee productivity and critical thinking based on demographic characteristics, employment status and years of service. Keywords: entrepreneurial intention, critical thinking, employee productivity, Telecommunication Company of Isfahan JEL Classifications: C32; O13; O47